UANG SEBAGAI PENGGANTI HEWAN QURBAN: KAJIAN FIQH KONTEMPORER - Dintara Lubis, Syaddan; Iqbal Irham, Muhammad; Faisal Hamdani, Muhammad (Penerbit Lafadz Jaya, 2025)
The tradition of qurban in Islam according to sharia is realized through the slaughter of livestock as a form of approaching Allah and social solidarity. However, in modern developments, a form of qurban diversion has emerged from animal slaughter to cash transfer to those in need. This study aims to analyze the phenomenon of